Dielectric spectroscopic sensor for particle contaminant detection in hydraulic fluids. Issue 1 (2nd January 2017) - Kshetri, Safal; Steward, Brian L.; Birrell, Stuart J.
Abstract: A practical contaminant sensor was developed that used dielectric spectroscopy to estimate levels of particles in hydraulic fluids. This dielectric sensor was designed for installation on off-highway vehicles to provide on-line estimates of hydraulic fluid cleanliness. Tests were performed using iron powder and ISO test dust as hydraulic fluid contaminants to investigate the performance of the sensor. An eight-channel particle counter was used for calibration of the dielectric sensor. Partial least squares regression models were developed to investigate the relationship between dielectric spectra and contaminant particle counts. The root mean square error of calibration (RMSEC) and root mean square error of cross validation (RMSECV) for the sensor with a central rod diameter of 6.35 mm were 1.1 and 1.39 of adjusted ISO fluid cleanliness codes, respectively, for iron powder. For a 17.7 mm diameter central rod, the respective RMSEC and RMSECV values were 0.62 and 0.83 for iron powder, and 1.29 and 1.48 for ISO test dust. The hydraulic fluid cleanliness level relative to particular particle contaminants can be determined by continuously monitoring fluid properties. The sensor shows good potential for estimating the cleanliness level of hydraulic fluid in the context of particle contaminants.